Evaluasi Implementasi Teknologi Informasi dalam Proses Pembelajaran di Sekolah Kabupaten Belitung: Antara Inovasi dan Kesiapan Sumber Daya - Eka Indah Wahyuni (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Digital transformation in education has encouraged the integration of information technology as an essential component of the teaching and learning process. However, the implementation of educational digitalization has not been evenly distributed, particularly in archipelagic regions that face infrastructural limitations and geographical challenges. This study aims to evaluate the implementation of information technology in learning activities and to examine the readiness of educational resources in schools in Belitung Regency. A quantitative approach with a descriptive-evaluative method was employed. Data were collected from 150 respondents, consisting of teachers and students from five schools, through Likert-scale questionnaires, observations, and documentation. Data analysis was conducted using descriptive statistics and Pearson correlation analysis. The results indicate that the level of information technology implementation is categorized as high, while the readiness of educational resources is also high, despite infrastructural support remaining at a moderate level. Correlation analysis reveals a strong positive relationship between information technology implementation and educational resource readiness. These findings suggest that teacher motivation and competence, school culture, and institutional policy support are capable of compensating for existing technical limitations. This study contributes to the literature by offering a holistic evaluative approach that assesses the success of educational digitalization not only in terms of technological availability, but also through the integration of human resource readiness, pedagogical practices, and local policy contexts in archipelagic regions.